PENGARUH WORKING CAPITAL TURNOVER, STRUCTURE ASSETS DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN - Lilis Karyawati; Esa Kurnia (Nindikayla Institute, 2023)
Processing of data on the financial statements of PT. Kalbe Farma Tbk for the 2015-2019 period, several periods were not by the theory, namely 9 periods with problems in Working Capital Turnover and Structure Assets and 10 periods in Debt to Equity Ratio. This study aims to determine and analyze the effect of the variable Working Capital Turnover, Structure Assets and Debt to Equity Ratio partially and simultaneously on the Net Profit Margin. The results showed that the effect of Working Capital Turnover partially had no significant effect on Net Profit Margin with an R-Square value of 11.4%. The influence of Structure Assets on Net Profit Margin partially has a significant effect on Net Profit Margin with an R-Square value of 56.4%. The influence of the Debt to Equity Ratio partially has a significant effect on the Net Profit Margin with an R-Square value of 22.6%. The effect of Working Capital Turnover, Structure Assets, and Debt to Equity Ratio on Net Profit Margin simultaneously has a significant effect on Net Profit Margin with an R-Square value of 58.2%, hypothesis testing shows Fcount > Ftable, then H0 is rejected and Ha is accepted